Critical role of the circadian clock in memory formation: lessons from Aplysia - Lyons, Lisa C. (Frontiers in Molecular Neuroscience, 2011)
Unraveling the complexities of learning and the formation of memory requires identification of the cellular and molecular processes through which neural plasticity arises as well as recognition of the conditions or factors through which those processes are modulated. With its relatively simple nervous system, the marine mollusk Aplysia californica has proven an outstanding model system for studies of memory formation and identification of the molecular mechanisms underlying learned behaviors, including classical and operant associative learning paradigms and non-associative behaviors. In vivo behavioral studies in Aplysia have significantly furthered our understanding of how the endogenous circadian clock modulates memory formation. Sensitization of the tail-siphon withdrawal reflex represents a defensive non-associative learned behavior for which the circadian clock strongly modulates intermediate and long-term memory formation. Likewise, Aplysia exhibit circadian rhythms in long-term memory, but not short-term memory, for an operant associative learning paradigm. This review focuses on circadian modulation of intermediate and long-term memory and the putative mechanisms through which this modulation occurs. Additionally, potential functions and the adaptive advantages of time of day pressure on memory formation are considered. The influence of the circadian clock on learning and memory crosses distant phylogeny highlighting the evolutionary importance of the circadian clock on metabolic, physiological and behavioral processes. Thus, studies in a simple invertebrate model system have and will continue to provide critical mechanistic insights to complementary processes in higher organisms.